Analisis Semiotika Sampul Buku Soulscape Road Karya Oscar Motuloh - Desintha, Siti (Universitas Komputer Indonesia, 2019)
Soulscape Road is one of the compilations of Oscar Motuloh's work against the background of the disaster that occurred in Indonesia. Photographs of spot or news photos are recorded in essays in the social and cultural context of Oscar Motuloh as a journalist. Book Cover is basically an information that represents the contents of a book. Book Cover as a point of interest gives the perception and image formed through the visual. Soulscape Road book Cover by Oscar Motuloh has a distinctive character by using several media (mix media) as its illustration and becoming a differentiator with general book Covers. The study was conducted to determine the image relation or image of the sign construction on the book's Cover. This study uses a descriptive method, with the Peirce semiotic approach